New fossil assemblages from the Early Ordovician Fezouata Biota - Farid Saleh; Romain Vaucher; Muriel Vidal; Khadija El Hariri; Lukáš Laibl; Allison C. Daley; Juan Carlos Gutiérrez-Marco; Yves Candela; David A. T. Harper; Javier Ortega-Hernández; Xiaoya Ma; Ariba Rida; et al. (Scientific Reports, 2022)
Abstract The Fezouata Biota (Morocco) is a unique Early Ordovician fossil assemblage. The discovery of this biota revolutionized our understanding of Earth’s early animal diversifications—the Cambrian Explosion and the Ordovician Radiation—by suggesting an evolutionary continuum between both events. Herein, we describe Taichoute, a new fossil locality from the Fezouata Shale. This locality extends the temporal distribution of fossil preservation from this formation into the upper Floian, while also expanding the range of depositional environments to more distal parts of the shelf. In Taichoute, most animals were transported by density flows, unlike the in-situ preservation of animals recovered in previously investigated Fezouata sites. Taichoute is dominated by three-dimensionally preserved, and heavily sclerotized fragments of large euarthropods—possibly representing nektobenthic/nektic bivalved taxa and/or hurdiid radiodonts. Resolving whether this dominance reflects a legitimate aspect of the original ecosystem or a preservational bias requires an in-depth assessment of the environmental conditions at this site. Nevertheless, Taichoute provides novel preservational and palaeontological insights during a key evolutionary transition in the history of life on Earth.